2013
DOI: 10.1007/s11524-013-9828-5
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing a Violent Death and Smoking, Alcohol Consumption, and Marijuana Use among Adolescents

Abstract: Witnessing violence has been linked to maladaptive coping behaviors such as smoking, alcohol consumption, and marijuana use. However, more research is required to identify mechanisms in which witnessing violence leads to these behaviors. The objectives of this investigation were to examine the association between witnessing a violent death and smoking, alcohol consumption, and marijuana use among adolescents, to identify whether exhibiting depressive symptoms was a mediator within this relationship, and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Several studies have been conducted among school-based populations to assess the relationship between a reduced set of violent events and cigarette smoking. In these studies, from China, Malawi, the United States, Chile, and the Western Pacific, bullying or being involved in physical fights was significantly associated with cigarette use [ 21 25 ]. A cross-country school-based study showed a consistent association between physical fights and cigarette smoking in 6 countries within the Western Pacific [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted among school-based populations to assess the relationship between a reduced set of violent events and cigarette smoking. In these studies, from China, Malawi, the United States, Chile, and the Western Pacific, bullying or being involved in physical fights was significantly associated with cigarette use [ 21 25 ]. A cross-country school-based study showed a consistent association between physical fights and cigarette smoking in 6 countries within the Western Pacific [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for poor outcomes in adolescence include poverty, being raised by a single parent, being born to a teenage mother, living in a ‘foster’ household, parental alcoholism and being abused mentally or physically 1, 2. These risk factors are paired with lower academic achievement, incarceration, teen pregnancy, increased mental illness and violence after controlling for sex, race/ethnicity and education 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Other published ndings (Table 6) [27]. Regarding gender differences, one study showed that boys who witnessed a violent death were signi cantly more likely to smoke compared with girls [25], but another study showed no signi cant differences between girls and boys who were involved in bullying or a physical ght [23]. None of these studies asked about family violence nor were conducted in areas with long-term armed con icts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted among school-based populations to assess the relationship between a reduced set of violent events and cigarette smoking. In these studies, from China, Malawi, the United States, Chile, and the Western Paci c, bullying or being involved in physical ghts was signi cantly associated with cigarette use [21] [22][23] [24] [25]. A cross-country school-based study showed a consistent association between physical ghts and cigarette smoking in 6 countries within the Western Paci c [26].…”
Section: Introductionmentioning
confidence: 99%